2021
DOI: 10.1108/ejmbe-06-2020-0169
|View full text |Cite
|
Sign up to set email alerts
|

Bitcoin and CEE stock markets: fresh evidence from using the DECO-GARCH model and quantile on quantile regression

Abstract: PurposeThis study examines the inter-linkages between Bitcoin prices and CEE stock markets (Hungary, the Czech Republic, Poland, Romania and Croatia).Design/methodology/approachThe dynamic contemporaneous nexus has been analyzed using both the multivariate DECO-GARCH model proposed by Engle and Kelly (2012) and quantile on quantile (QQ) methodology proposed by Sim and Zhou (2015). Our study is implemented using the daily data spanning from 6 September 2012 to 12 August 2019.FindingsFirst, the findings show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Financial markets have made significant progress in terms of volume and magnitude in recent years, thanks to the emergence of a wide range of cryptocurrencies and various innovative financial instruments. This remarkable development in financial markets has also increased risk and compelled global investors to seek out a safe haven investment (Hung, 2021b). Bitcoin, which captures public interest, is the well-known currency in virtual financial asset markets.…”
Section: Introductionmentioning
confidence: 99%
“…Financial markets have made significant progress in terms of volume and magnitude in recent years, thanks to the emergence of a wide range of cryptocurrencies and various innovative financial instruments. This remarkable development in financial markets has also increased risk and compelled global investors to seek out a safe haven investment (Hung, 2021b). Bitcoin, which captures public interest, is the well-known currency in virtual financial asset markets.…”
Section: Introductionmentioning
confidence: 99%
“…The second series of research looked at how businesses reacted to COVID-19 (see also, Didier et al, 2021;Gu et al, 2020;Meyer et al, 2021). COVID-19's influence on other aspects of the financial system is the subject of the third set of research (see Adam et al, 2022;Agyei et al, 2021;Asafo-Adjei et al, 2021;Boateng et al, 2021;Cox et al, 2020;Liu et al, 2020;Mazur et al, 2021;Owusu Junior et al, 2021;Zeren and Hizarci, 2020;Hung, 2021). The results from the empirical literature have been largely varying across markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Hung (2021) found that Bitcoin has an average positive correlation with the stock market of CEE (Croatia, Hungary, Poland, Romania, and the Czech Republic), using the Dynamic Equi-correlation GARCH (DECO-GARCH) model. Omane-Adjepong et al.…”
Section: Content Analysismentioning
confidence: 99%
“…This part will discuss some of their findings. Hung (2021) found that Bitcoin has an average positive correlation with the stock market of CEE (Croatia, Hungary, Poland, Romania, and the Czech Republic), using the Dynamic Equi-correlation GARCH (DECO-GARCH) model. Omane-Adjepong et al ( 2021) found an asymmetric herd behaviour in the cryptocurrency and stock markets of 10 emerging economies within G20 conducting the cross-sectional absolute deviation (CSAD) approach.…”
Section: Othersmentioning
confidence: 99%